2019
DOI: 10.5380/raega.v46i1.59160
|View full text |Cite
|
Sign up to set email alerts
|

Fatores De Perturbação Identificados Em Área De Proteção Ambiental Corumbataí-Botucatu-Tejupá, Perímetro Botucatu, Estado De São Paulo

Abstract: As imagens de satélite de alta resolução espacial se tornaram muito importantes na análise, interpretação e quantificação das transformações ambientais ocorridas ao longo do tempo, permitindo o monitoramento da dinâmica do uso e ocupação do solo, e o monitoramento de áreas protegidas por lei, promovendo instrumentos para um desenvolvimento sustentável, que concilia a produção agrícola e a proteção dos recursos naturais. O presente trabalho é uma análise espacial dos fatores de perturbação e seus potenciais imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Before the project, the use of area for agriculture, specifically pasture, cattle trampling within 50 m radius from the spring's APP, causing soil compaction, silting and high degradation condition. Pollo et al (2019) evaluated disturbance factors in an environmental protection area and concluded that changes in vegetation coverage caused by agricultural activities became the region susceptible to environmental degradation processes, generating fragile water resources, such as irregular land occupation in areas of environmental preservation and silting of water bodies.…”
Section: Analysis Of Environmental Quality Indicatorsmentioning
confidence: 99%
“…Before the project, the use of area for agriculture, specifically pasture, cattle trampling within 50 m radius from the spring's APP, causing soil compaction, silting and high degradation condition. Pollo et al (2019) evaluated disturbance factors in an environmental protection area and concluded that changes in vegetation coverage caused by agricultural activities became the region susceptible to environmental degradation processes, generating fragile water resources, such as irregular land occupation in areas of environmental preservation and silting of water bodies.…”
Section: Analysis Of Environmental Quality Indicatorsmentioning
confidence: 99%
“…Permite identificação de áreas agrícolas(SILVA et al, 2019d).B8: 0,85-0,88Identificação e delineamento de corpos d'água. Sensibilidade à rugosidade de dossel florestal e de terreno(POLLO et al, 2019). Permite identificação de macrófitas aquáticas e de áreas agrícolas(MINHONI et al, 2015).O Landsat-8/OLI apresenta alta resolução espacial (comparado ao MODIS) e possibilita análises a nível de propriedade rural, principalmente quando ocupada por talhões com dimensões laterais maiores que 30 metros.4.3 MISSÃO SENTINEL Os satélites Sentinel 1 até 5 foram projetados especificamente para monitoramento ambiental (VAN DER WERFF, VAN DER MEER, 2015) e lançados em 2015.…”
unclassified